PENGEMBANGAN LKPD BERBASIS REACTPADA MATERI PESAWAT SEDERHANA DALAM PEMBELAJARAN IPA SMPN 25PEKANBARU - Dwi Satya Agustina; Zulirfan Zulirfan; Muhammad Syafii (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:REACT strategy is a learning strategy in a contextual approach, to impelement the REACT learning strategy, We have developed a set of studentlyworksheetbased on REACT theworksheet that is compiled and designed with emphasis on the interrelationship between subjectmatter and the real world of student’s life. The purpose of this study was to develop a valid physical LKPD based on REACTon simple machinematerial injuniorhigh school science learningIn this study, the validation stage was carried out by 3 lecturers of Physics Education who were experienced and also conducted trials limited to 10students of class VIIIat SMPN 25Pekanbaru. The research instrument was in the form of a questionnaire shaped a checklist. Data analysis in this study used descriptive analysis by calculating the index of each indicator used to determine the validity of the develop LKPD. The results of this study provide information that the developed of physical LKPD based on REACT in simple machinematerialis valid and practical in the high and very high categories and can be used in learning to support the teaching and learning process so that it becomes better.KeyWords:LKPD,REACT, Simple Machine, Science Learning.